2007
DOI: 10.1109/tmag.2006.887688
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Compensation and Improved Ballistic Performance in a Solid-Propellant Electrothermal-Chemical (SPETC) 40-mm Gun

Abstract: A solid-propellant electrothermal-chemical (SPETC) 40-mm gun has been designed, constructed, and tested in the indoor firing facilities of the Soreq Propulsion Division Laboratory. An external injector device converts the electric energy stored in the capacitors of the pulse forming network (PFN) into a high-temperature plasma jet that penetrates the gun cartridge and boosts the whole ballistic process. However, unlike large-caliber SPETC systems, in which electric energy is limited to ignition purposes, the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Some of the other uses for electrothermal plasmas are for artillery propellants [4,5], thrusters for spacecraft or satellite applications [6][7][8], hypervelocity launchers [9][10][11], and high heat flux applications [12,13].…”
Section: Electrothermal Capillary Pellet Injectormentioning
confidence: 99%
“…Some of the other uses for electrothermal plasmas are for artillery propellants [4,5], thrusters for spacecraft or satellite applications [6][7][8], hypervelocity launchers [9][10][11], and high heat flux applications [12,13].…”
Section: Electrothermal Capillary Pellet Injectormentioning
confidence: 99%
“…In the past decades, a variety of technical approaches and regulatory mechanisms have been developed to obtain a low temperature sensitivity coefficient. Electrothermal chemical launcher technology [8,9] reduces the influence of temperature on the linear burning rate of propellants by adjusting the input electric energy [10,11]. Another regulatory mechanism is to compensate the decreasing burning rate by increasing burning surface of the propellant, such as prefabrication of microcracks [12][13][14], SCDB (surface coated double base) [15,16], ECL (extruded composite low sensitivity) [17,18] and EI (extruded impregnated) technologies [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Mario Štiavnicky et al experimented with various composite materials to fabricate armour for the arm at 50 mm thickness with a lighter weight than other materials. They found that Kevlar fabric reduced the speed of a bullet MJ of power from a 1 GW power source increased the propulsion of a 300-gr projectile by 20% [3]. Finite element analysis (FEA) is often used for behavioral studies of variously-shaped bullets.…”
Section: Introductionmentioning
confidence: 99%